Inaction over retractions of identified fraudulent publications: ongoing weakness in the system of scientific self-correction. (19th May 2018) - Wiedermann, Christian J.
ABSTRACT: Published articles may be retracted when their findings are no longer considered reliable due to honest error, publication misconduct, or research misconduct. This article focuses on the case of a single serial violator of research and publication ethics in anesthesiology and critical care, which is widely publicized. A chain of events led to detection of misconduct that had substantial impact on the evidence base for the safety of hydroxyethyl starch, an intravenous artificial colloid solution, which is reflected in current guidelines on fluid management and volume resuscitation. As citations to retracted works continue to be a cause for concern, this article reviews the retraction status of this author's published articles to determine whether sufficient action has been taken to retract his body of work. Results show that retraction practices are not uniform and that guidelines for retraction are still not being fully implemented, resulting in retractions of insufficient quantity and quality. As retractions continue to emerge for the author's publications, with ten more since 2011, and as they are generally increasing, these data on retractions not only provide findings of misconduct, but also allow us to make inferences about ongoing weaknesses in the system of scientific literature.